Los epodos eróticos de Horacio y los inicios de la elegía latina - Alvar Ezquerra, Antonio, 1954- (Estudios clásicos, 1997)
Erotical Epods of Horatius present a great number of topics similar to those of the further Latin love Elegy. That can¿t be casual and rather may be an ironic or parodic answer to a literary genre and to a form of conceiving love very different from Horatius' erotical points of view.